Language, Visuality and Representation of Nigeria - China Relations in Nigerian Digital Space - Onanuga, Paul; Gbadegesin, Victoria O. (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Nigeria – China relationship has witnessed significant upsurge in the last decade. The budding relationship however continues to attract diverse perceptions as reflected in digital spaces. In this study, ten images – cartoons – from the Internet were subjected to Multimodal Critical Discourse Analysis. The depictions of Chinese influence and activities in Nigeria are engaged and representations that oscillate from financial/economic concerns to issues around sociality and culture are identified. Within the discourses around economy, China is revealed as a superpower attempting to exert its influences through subtle force to take over national sovereignty, while Nigerian leaders are shown as complicit in the exploitation of their citizens. In the context of sociality and culture, China is represented as a thriving society which is worthy of emulation although issues around racism and discrimination are also tackled. The diversity of representations manifests the complications that continue to engage issues of globalisation, fear of domination, and China’s rise in Africa.